Zinc finger protein 184 prevents α-synuclein preformed fibril-mediated neurodegeneration through the interleukin enhancer binding factor 3-microRNA-7 pathway - Jihye Kim; Soojeong Park; Jee-Ho Lee; Ji-Yeong Lee; Joo-Ho Shin (PLoS ONE, 2025)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by a loss of dopaminergic neurons. Recent studies suggested the association of zinc finger protein 184 (ZNF184) with PD. However, the functional role of ZNF184 in PD pathogenesis remains unclear. Therefore, we aimed to confirm this association and the effects of ZNF184 in a mouse model of PD and human patients with PD. We found that ZNF184 levels were decreased in the substantia nigra (SN) of α-synuclein preformed fibril (α-syn PFF)-injected mice and cells treated with PD toxins. Furthermore, ZNF184 was reduced in the cortex and SN of patients with PD, suggesting an association between ZNF184 and PD pathogenesis. In ZNF184-overexpressing cells, RNA-sequencing analysis revealed significant alterations in several protein-coding genes including interleukin enhancer binding factor 3 (ILF3). Bioinformatic analysis identified potential ZNF184 binding motifs within the ILF3 promoter, and ZNF184 occupancy was confirmed. Since ILF3 inhibits the biogenesis of microRNA-7 (miR-7), which regulates α-synuclein aggregation, we administered the miR-7 inducer, scutellarin to α-syn PFF-injected mice, preventing dopaminergic neuron and reinstating motor abilities. Our findings suggest that ZNF184 promotes miR-7 upregulation by suppressing ILF3 transcription, revealing a novel pathway that could serve as a promising therapeutic target for the treatment of PD.